A study on the perceptions of University of the Philippines Diliman College of Science faculty members on the use of open access journals - Tadique, Rocelle S. (School of Library and Information Studies, University of the Philippines Diliman, 2009)
The increasing costs of traditional print journals prompted publishers and users to find new ways to publish journals in cheaper ways. With the advent of the use of the Internet as a tool for disseminating information, the open access movement was initiated and intensified. The main goal of the movement was to publish articles online for free to the public worldwide. The results were the publication of open access journals, which were voluntarily published by the authors, were peer-reviewed, and were free for accession and use by the end users.